Intersections between informal social and economic systems in Ghana: transformations and implications for managing economic hardship - Theodora Akweley Asiamah (Cogent Arts & Humanities)
Informal social and economic systems of kinship, labour relations, child fostering, food sharing and shelter sharing have characterized African societies. These arrangements have played significant roles in household risk management in Ghana in previous times and are still relevant in the management of economic hardships. Within the context of rapid globalisation and modernisation, these social and economic arrangements have changed over time, with some dire ramifications including economic hardships. Using secondary data consisting of literature sources, this paper examines these informal social and economic systems, highlighting their underlying concepts, transformations, and relevance in the prevention and management of risks associated with care, labour, and poverty. The author finds reciprocity and solidarity as the dominant underlying concepts of the social and economic systems understudied. Further, there were transformations in these arrangements contributed by factors, such as scarcity of resources, modernisation, weakening of kinship ties, unmanaged urbanisation, economic monetisation, and economic development. The paper recommends the incorporation of underlying concepts, such as reciprocity and solidarity in social protection policies for sustainable management of risks and economic hardships in the future. This will support poverty reduction efforts and the attainment of the Sustainable Development Goal 1 (SDG1).